Family caregivers coping with terminality during home care - Stefanie Griebeler Oliveira; Alberto Manuel Quintana; Maria de Lourdes Denardin Budó; Maria Henriqueta Luce Kruse; Raquel Pötter Garcia; Bruna Sodré Simon (Universidade Federal do Ceará, 2013)
This study aimed to know how family caregivers cope with the finitude of their close relative in home care. This is a qualitative study, involving 11 caregivers of terminally ill patients, registered in a home care service of a university hospital in the South of Brazil, conducted in the period from January to June 2010. Data collection occurred through narrative interviews which were recorded and transcribed to be analyzed through content analysis. Two categories emerged from data analysis: "feelings involved in terminally ill patients home care" and "repercussions of human finitude in the caregiver's life", which made clear the complexity of home care of patients without possibilities of cure and the sufferings incurred by this situation to the family caregivers that are responsible for a caring of this nature.